Research on the Differential Mechanisms of Knowledge Cross-Border Searching on Firms’ Dual Innovation in the Digital Context: Based on Simulation of System Dynamics Model - Zhou Huiping; Yang Yuxin (Discrete Dynamics in Nature and Society)
Acquiring and combining heterogeneous knowledge resources across organizational boundaries are an important path for the success of enterprises’ innovation. From the perspective of the relation attributes between knowledge elements, this paper divides knowledge cross-border searching into two types: domain knowledge searching and architectural knowledge coupling searching. Then, we construct a system dynamics model and use Vensim PLE software to carry out simulation analysis to explore the differential mechanisms of knowledge cross-border searching influence firms’ dual innovation in the context of digital transformation. The analysis results show that domain knowledge searching positively affects firms’ iterative innovation, while there is an inverted U-shaped relationship between architectural knowledge searching and firms’ disruptive innovation, indicating that different types of knowledge cross-border searching have differential effects on firms’ dual innovation. The simulation results also address that digital resources can promote enterprises' dual innovation in the process of knowledge cross-border searching. The research results reveal that the internal laws of knowledge cross-border searching affect enterprises' dual innovation in the context of digital transformation and provide a theoretical reference for enterprises to effectively use digital technology to adopt knowledge searching activities.